Nonparametric Stability Analysis of Starch Content of Gamma Irradiated Cassava at Three Locations in West Java, Indonesia - Agustina, Ferra Anggita; Khumaida, Nurul; Ardie, Sintho Wahyuning; Syukur, Muhamad (Journal of Tropical Crop Science, 2020)
Cassava is one of the largest starch producing tuber crops in Indonesia. Tapioca from cassava starch can be used as a raw materials for a variety of foods including biscuits, instant porridge, meatball, sausage, nuggets, and flour condiment. Breeding programs to improve cassava yield and starch content by using mutagen gamma rays irradiation was tested in four cassava generations (M1V4). Cassava is propagated by stem cuttings and the new characteristic obtained from gamma irradiation mutation is stable and can be passed from one generation to the next. Cassava mutants were obtained by evaluating the performance in different environmental conditions. The testing of yield adaptability and stability through a series of multi location is an important step before a new variety can be released. The aim of this research was to compare nonparametric stability and to evaluate the stability of the starch content of 16 genotypes (14 mutants and 2 varieties) in three locations in West Java Province i.e. Tapos (Depok), Cikarawang (Bogor), and Ciseeng (Bogor). Experiments were conducted in a completely randomized block design with three replications nested in each environment. Testing of yield stability in this study used four approaches with 10 parameters of nonparametric method. Starch content was estimated using gravimetric method. Based on frequency stability ranking of starch content from gravimetric method the G63142 genotype had the highest starch content estimation (29.99%), and the top five genotypes with high starch content were G63142, G61142, “Manggu”, G62151, and G63124. G61142 was categorized as genotype with static and dynamic stability, therefore this genotype is a very potential mutant to be released, whereas G63124 is categorized as a genotype with a static stability. Genotypes G63142, G62151, and “Manggu” had variable but relatively high starch content.